Prilidiano Pueyrredón - Luna, Félix; Amigo, Roberto; Giunta, Patricia (Buenos Aires : Banco Velox, 1999)
Ensayo histórico de: Luna, Félix. Estudios críticos de: Amigo, Roberto y Giunta, Patricia Laura
Keywords: ARTISTAS; PINTORES; SIGLO XIX; PUEYRREDON, PRILIDIANO; ARQUITECTOS; ARGENTINA